The Application of Technology in Enhancing Safety and Health Aspects on Malaysian Construction Projects - Nurhidayah, Azmy; Ahmad Zairi, Mohd Zain (Asian Research Publishing Network (ARPN), 2016)
Construction industry is commonly known as an industry exposed to high risks in many aspects, especially related to safety and health. Despite many efforts done by all relevant parties related to the construction industry to bring awareness and enhancing the level of safety and health in construction projects, accidents keep on occurring on construction sites. Safety procedures, policies and regulations may already be implemented on-site; however, the effectiveness of its implementation is still debatable. The use of technology has proven to help in minimizing number of accidents occurrence on construction site and overall construction safety management. This paper provides an overview of various types of technology applications (3D and 4D visualisation techniques, information and communication technology, real-time tracking systems, RFIDs and remote-sensing) suitable for effective implementation and improvisation on construction jobsite that have been proposed and studied by numerous researchers worldwide based on the traditional review conducted. The information gathered can be used to determine some of the applications that can be implemented on Malaysian construction projects. The technology proposed may effectively help construction players to reduce number of accidents and thus, elevate the safety and health aspects in Malaysian construction industry to another level.